Immunological study on the effect of some free radicals and antioxidants on the placenta of pregnant women with rheumatic heart diseases - Al-Assaf, Anwar Idrees Sulaiman; Al-Rubai, Ragwa H.I.; Al-Ani, Imad Matloub Dally; Al-Ubaidi, Salim Rasheed (Department of Anatomy, National University of Singapore, 2014)
Introduction: The present study was undertaken to assess the role of heart diseases on pregnancy status. Twenty-six pregnant women with rheumatic heart disease (RHD), fi ve pregnant women with non rheumatic heart disease (NRHD) and ten healthy pregnant control groups were investigated. Methods: Immunological responses were investigated, and the activity of adenosine deaminse (ADA) was measured. Radial immunodiffusion (RID) technique, was used to quantify the immunoglobulin level, such as, IgG ,IgM and IgA , in addition to the complement components C3 and C4 , in serum and placental tissue, blood films with Leishman’s stain and the granulocytes were prepared. Results: The results indicated that there is a signifi cant depression in tissue IgG and IgA levels in patients as compared with control groups, while the level of IgM is very low in tissue and less than normal value. Serological tests such as, anti streptolycinO–titer (ASO-T ) , venereal disease research laboratories ( VDRL ) , anti - nuclear antibody ( ANA ) and anti - cardiolipin antibody ( ANCA ) gave negative results except for two cases with positive (ASO-T ) titers.